Do individuals recognize cascade behavior of others? An experimental study - Tim Grebe; Julia Schmid; Andreas Stiehler (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2006)
In an information cascade experiment participants are confronted with artificial predecessors predicting in line with the BHW model (Bikchandani et al. 1992). Using the BDM (Becker et al., 1964) mechanism we study participants' probability perceptions based on maximum prices for participating in the prediction game. We find increasing maximum prices the more coinciding predictions of predecessors are observed, regardless of whether additional information is revealed by these predictions. Individual price patterns of more than two thirds of the participants indicate that cascade behavior of predecessors is not recognized.
Keywords: C91; D81; D82; 330; information cascade; Bayes' Rule; decision under risk and uncertainty; experimental economics; Informationsökonomik; Spieltheorie; Test; Entscheidung; Theorie